2022
DOI: 10.3389/pore.2022.1610592
|View full text |Cite
|
Sign up to set email alerts
|

Stat3 Tyrosine 705 and Serine 727 Phosphorylation Associate With Clinicopathological Characteristics and Distinct Tumor Cell Phenotypes in Triple-Negative Breast Cancer

Abstract: Signal transducer and activator of transcription 3 (Stat3) is responsible for many aspects of normal development and contributes to the development and progression of cancer through regulating epithelial cell identity and cancer stem cells. In breast cancer, Stat3 is associated with triple-negative breast cancers (TNBC) and its function has been related to the activation of p63, itself a marker of basal-like TNBC and a master regulator of stem cell activities. Stat3 activation is controlled by dual phosphoryla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 60 publications
0
2
0
Order By: Relevance
“…Overall, we hereby reveal novel information on the functional consequences of Y705-STAT3 and p65 activation, and on the regulation of STAT3 activation at the expression level as well as through its post-translational modifications at the Y705 vs. the S727 sites, which have been described previously to have different effects of cell functions [ 81 , 84 ]. Eventually, the complex network established by STAT3 and p65 in regulating CSC enrichment upon TME Stimulation may have strong clinical implications, as we have noted by the studies on doxorubicin resistance and clinical data from luminal A patients.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…Overall, we hereby reveal novel information on the functional consequences of Y705-STAT3 and p65 activation, and on the regulation of STAT3 activation at the expression level as well as through its post-translational modifications at the Y705 vs. the S727 sites, which have been described previously to have different effects of cell functions [ 81 , 84 ]. Eventually, the complex network established by STAT3 and p65 in regulating CSC enrichment upon TME Stimulation may have strong clinical implications, as we have noted by the studies on doxorubicin resistance and clinical data from luminal A patients.…”
Section: Discussionmentioning
confidence: 68%
“…This study also demonstrated that consistent activation of STAT3 at the Y705 site conferred in prostate cancer cells a differentiated epithelial morphology, and that STAT3 loss induced a mesenchymal-like phenotype and higher tumor cell aggressiveness [ 80 ]. Moreover, a 2022 study of TNBC breast cancer patients demonstrated that high phosphorylation levels of Y705-STAT3 were associated with epithelial cell phenotype and luminal differentiation markers which are generally connected to lower levels of CSCs; in contrast, high phosphorylation levels of STAT3 at the S727 site were connected to a basal phenotype [ 81 ].…”
Section: Discussionmentioning
confidence: 99%